The Human G Protein-Coupled ATP Receptor P2Y11 Is Associated With IL-10 Driven Macrophage Differentiation - Gruenbacher, Georg; Gander, Hubert; Rahm, Andrea; Dobler, Gabriele; Drasche, Astrid; Troppmair, Jakob; Nussbaumer, Walter; Thurnher, Martin (Frontiers in Immunology, 2019)
The G protein-coupled P2Y11 receptor is known to sense extracellular ATP during inflammatory and immune responses. The dinucleotide NAD+ has also been proposed to be a P2Y11 receptor ligand but its role is less clear. Here, we have examined for the first time human P2Y11 receptor protein levels and show that the receptor was upregulated during polarization of M2 macrophages. IL-10 reinforced P2Y11 receptor expression during differentiation of M2c macrophages expressing CD163, CD16 and CD274 (PD-L1). Nutlin-3a mediated p53 stabilization further increased P2Y11 receptor, CD16 and PD-L1 expression. AMP-activated kinase (AMPK), which mediates anti-inflammatory effects of IL-10, and nicotinamide phosphoribosyl¬transferase (NAMPT), the rate-limiting enzyme of the NAD+ salvage pathway, which is under the control of AMPK, were also required for P2Y11 receptor expression. The P2Y11 receptor agonist ATPγS and NAD+ could independently stimulate the production of IL-8 in M2 macrophages, however, only the ATPγS-induced response was mediated by P2Y11 receptor. Both in a recombinant system and in macrophages, P2Y11 receptor-driven IL-8 production predominantly depended on IKB kinase (IKK) and extracellular signal–regulated kinase (ERK). In conclusion, our data indicate that an AMPK-NAMPT-NAD+ signaling axis promotes P2Y11 receptor expression during M2 polarization of human macrophages in response to IL-10. PD-L1 expressing M2c macrophages that secrete the cancer-promoting chemokine IL-8 in response to P2Y11 receptor stimulation may represent an important target in checkpoint blockade immunotherapy.